Collane e paratesto nel processo traduttivo: come i libri per bambini assumono una nuova identità nel sistema letterario di arrivo - Melissa Garavini (Strenae)
When children’s books travel from the source literary system to the target one, not only is the written text translated or adapted but also other elements, such as the paratextual ones, are often deeply affected in order to make a work acceptable by the target audience. Indeed, the insertion of a book in a particular series (in its function as paratext) renders the work more easily identifiable – to adults – with specific editorial conventions of the literary production for children such as the age recommendation, the written style, and the layout. These are the elements which guide adult buyers and may be decisive to a children’s book editorial success or failure.Since such editorial conventions usually belong to a specific literary system and therefore may vary from culture to culture, the study of paratextual elements in translation is becoming more and more significant and it is opening up new research opportunities. For this reason, this paper conducts an editorial study of how paratext is translated and adapted during the translation process. In particular, this paper firstly looks at how the paratext in picturebooks (series, covers and the titles, the back covers and the blurbs, as well as the size of the book itself) is adapted in order to meet cultural standards of the target literary system. Picturebooks written and illustrated by the Finnish author and illustrator, Mauri Kunnas, will be used as a case study together with the relevant translations into Italian. Secondly, the paper opens a discussion from a diachronic perspective of how the Italian publisher’s view has developed in the last three decades. Finally, the paper will reveal the different actors involved in the translation process showing that, although translations of children’s books are polyphonic works, the paratext clearly remains the area where the editor’s voice is more audible compared to the translator’s one.